Development of Productive Waqf in Candimulyo Village from an Islamic Law Perspective - Rokhani, Moh.; Syafi'i, Ahmad; Putri, Diyan Putri (Civiliza Publishing, 2024)
Istismari waqf is also commonly called productive waqf, which is a waqf of property used for investment purposes, either in agriculture, industry, trade, and services. The benefits of productive waqf are not obtained from the waqf object directly, but from the profits or results of waqf management. The word productive is an adjective derived from the word product which means results, work results, goods or objects that are produced. Based on this meaning, the word productive means something that has yield power or has the ability to produce (in large quantities). The formulation of the problem in this study is how is the strategy for developing productive rice field waqf in Candimulyo Village? And how is the development of productive rice field waqf in Candimulyo Village from an Islamic law perspective. This study aims to describe the strategy for developing productive rice field waqf in Candimulyo Village and to analyze the development of productive rice field waqf in Canimulyo Village from an Islamic law perspective. The research method used is field study with a qualitative approach. Data collection was carried out through interviews, observations, and documentation. Data analysis using descriptive-analytical methods. The results of the study show that: (1) The potential for productive waqf in Candimulyo Village is quite large, both in terms of land area, agricultural commodities, and the number of nazhirs. However, the management of productive waqf in this village is still not optimal. (2) From an Islamic legal perspective, the development of productive waqf in Candimulyo Village can be carried out through professional management, development of various types of productive businesses, and empowerment of the surrounding community. This is in line with the objectives of waqf in Islam, namely for the public interest and welfare of the community.